Comportamento de dípteros muscóides frente a substratos de oviposição, em laboratório, no Rio de Janeiro, RJ, Brasil Behavior of caliptrate diptera in relation to the choose of oviposition substrates under laboratory conditions in Rio de Janeiro, RJ, Brazil - José Mario d'Almeida; Rubens Pinto de Mello (Memorias do Instituto Oswaldo Cruz, 1996)
How adult females of calyptrate Diptera recognize the appropriate breeding substrate is a matter of controversy. Among holometabolic insects, the feeding opportunities of immature stages are generally determined by the adult female choice of an oviposition site. The ovipositional and larvipositional substrate preference for the synanthropic flies (Chrysomya megacephala, C. putoria, Phaenicia cuprina: Calliphoridae; Atherigona orientalis, Synthesiomyia nudiseta: Muscidae; Ravinia belforti, Parasarcophaga ruficornis, Peckia chrysostoma: Sarcophagidae) is presented in this work. The substrate used for testing were the following: bovine minced meat, fish (sardine), bovine liver, shrimp, squid, human faeces and banana. Bovine minced meat was the ovipositional and larvipositional substrate preferred by seven species. Human faeces were preferred by R. belforti.